Mechanismen und Tendenzen der kreativen Anpassung von IAW-Strukturen im Deutschen und im Französischen - Steven Schoonjans (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
German has a particularly large inventory of IAW structures, i.e. expressions such as zum Teufel ‘the devil’ and zur Hölle ‘the hell’ that are used as intensifiers in wh-questions. This is due to the fact that German maximally exploits the creative adaptation potential of IAW structures. French, on the other hand, has fewer IAW structures. However, as is shown in this paper, French has the same basic patterns according to which IAW structures are built and makes use of the same basic mechanisms for IAW modification that we also find in German, substitution and expansion. It thus seems that German simply makes more use of this adaptation potential that is also present in French. Still we also find some tendencies and restrictions in German, which also play a role in French. Two of them are discussed in more detail in this paper, viz. the preference for negatively connotated words and the role of the context and the community in which the IAW structures are used.